Numerical and experimental methods to investigate the behaviour of vertical-axis wind turbines with stators. Issue 144 (September 2015) - Burlando, M.; Ricci, A.; Freda, A.; Repetto, M.P.
Abstract: The practice of reproducing wind tunnel tests by means of CFD numerical simulations, which is known as numerical wind tunnel (NWT), is becoming quite common in many research fields of wind engineering. Wind tunnel tests can provide the indispensable validation data needed for CFD numerical simulations; at the same time, CFD can be considered a complementary support for wind tunnel tests in order to obtain a more comprehensive description of the flow field. In the present paper, NWT technique is applied to study the flow around and inside a multi-stage vertical-axis wind turbine (VAWT) surrounded by stator vanes. At first, the flow field has been studied in the wind tunnel by means of experimental tests. Then the experimental results have been used to validate a CFD model. The numerical model has finally been used to study and describe how the results obtained by means of the physical model can be extended to more general conditions.